PENGARUH VARIASI KONSENTRASI KARBOPOL 940 TERHADAP MUTU FISIK SEDIAAN EMULGEL EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) SEBAGAI TABIR SURYA SECARA In Vitro - Widitasari, Ayunda Syifa; Rejeki, Endang Sri; Purnamasari, Nur Aini Dewi (FKIP Universitas Tanjungpura, 2023)
Secondary metabolite like phenolic compounds found in kersen leaves have function to bind free radical. Emulgel is a preparation that is not greasy, spreads evenly, soft, and long lasting on storage. The objective of this study was to determine the physical quality of emulgel of kersen leave ethanol extract with various concentrations of carbopol 940, to determine the potential and effective concentration of carbopol 940 in emulgel of kersen leave ethanol extract as a sunscreen. This study used several formula with various concentration of carbopol 940 which is 1, 1.5, and 2%. Physical quality testing include organoleptic, homogeneity, spreading power test, adhesion test, pH test, and viscosity test. Determination of Sun Protecting Factor (SPF) value was carried out in vitro using UV-Vis spectrophotometry and Mansyur Calculation. The results obtained showed that emulgel of kersen leave ethanol extract with variations of the gelling agent carbopol 940 was stable for 21 days on storage and have activity as a sunscreen. Emulgel of kersen leave ethanol extract (Muntingia calabura L.) 1% concentration of carbopol 940 is the most effective as a sunscreen preparation with 25,42 SPF value which categories ultra protection.Keywords: kersen leave ethanol estrak, emulgel, sunscreen, SPF.